2020
DOI: 10.2139/ssrn.3733862
|View full text |Cite
|
Sign up to set email alerts
|

Income Loss and Financial Distress during COVID-19: The Protective Role of Liquid Assets

Abstract: Nearly a quarter of U.S. households have experienced job or income losses related to the COVID-19 pandemic. Liquid assets mitigate financial distress in the face of financial shocks such as job loss, yet this relationship in the midst of the COVID-19 pandemic is unknown. Using a nationally representative sample of U.S. households (N = 4,383) who completed a survey in the early days of the pandemic, we examined pre-pandemic liquid assets as a moderator of the relationship between job and income loss and difficu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 25 publications
1
26
0
2
Order By: Relevance
“…Many businesses were forced to shut down, and some small businesses closed permanently. While overcoming economic upheaval is helped markedly by an individuals' financial standing (85), COVID-19 affected such a large number of people with varying financial needs and capacities that financial distress for many was unavoidable. The positive correlation between financial distress and depressive symptoms has been identified in several studies [see (86)(87)(88)].…”
Section: Discussionmentioning
confidence: 99%
“…Many businesses were forced to shut down, and some small businesses closed permanently. While overcoming economic upheaval is helped markedly by an individuals' financial standing (85), COVID-19 affected such a large number of people with varying financial needs and capacities that financial distress for many was unavoidable. The positive correlation between financial distress and depressive symptoms has been identified in several studies [see (86)(87)(88)].…”
Section: Discussionmentioning
confidence: 99%
“…Nekatere študije posledic epidemije v nekaj evropskih državah so namreč pokazale, da zaradi različnih ukrepov finančne pomoči povečanje neenakosti ni nujno (Clark et al, 2020). So pa lahko takšne subjektivne ocene posledica dejstva, da so zaradi epidemije v različnih pogledih (zdravje, zaposlitev, šolanje …) bolj prizadeti tisti prebivalci, ki so že sicer prikrajšani (Roll in Despard, 2020). To pa pri ljudeh povzroča večjo finančno negotovost glede prihodnosti in posredno vpliva na njihove subjektivne zaznave v smislu povečanega občutka, da jim gre slabše od drugih.…”
Section: Subjektivni Družbeni Status In Odnos Do Neenakosti V čAsu Epidemijeunclassified
“…Postavljajo se vprašanja, katere skupine ali kategorije prebivalstva je zdravstvena kriza še posebej prizadela, ali so vsi deležni ustrezne zdravstvene obravnave, ali so se povečale dohodkovne neenakosti, ali prihaja do povečevanja revščine ter novih neenakosti med revnimi in bogatimi državami itd. Na ta vprašanja so poskušali odgovarjati različni raziskovalci, ki so se s svojimi študijami hitro odzvali na izbruh pandemije (Elgar et al, 2020;Clark et al, 2020;Roll in Despard, 2020; Fujimoto et al, 2021). V tem prispevku skušava odgovoriti na vprašanje, kaj se dogaja z zaznavami družbenih (dohodkovnih) neenakosti v kontekstu epidemije COVID-19 med prebivalci Slovenije.…”
unclassified
“…Shelter-in-place and other public health efforts introduced a national economic threat ( Bartik et al, 2020 ) that contributed to heightened financial stress ( Mann et al, 2020 ) and decreased ability to afford basic needs ( Roll and Despard, 2020 ). Early studies of pandemic effects showed that overall financial stress compromised family well-being during shelter-in-place ( Gassman-Pines et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%